Reducing academic burnout biology among boarding school students through LIVE (liveworksheet and videos) - Rohmatulloh, Ghina; Kusumastuti, Mimin Nurjhani; Kusnadi, Kusnadi; Pratiwi, Heti (JPBIO (Jurnal Pendidikan Biologi), 2025)
Academic burnout is a common issue among boarding school students due to demanding routines and high academic pressure, particularly in Biology classes, which involve many abstract concepts. This study aimed to examine the effectiveness of using LiveWorksheet and instructional videos in reducing the level of academic burnout among boarding school students. A one-group pre–post test design with two post-intervention measurements was employed. The sample consisted of senior high school boarding students who participated in Biology learning activities using a combination of LiveWorksheet and instructional videos. Data were collected using an academic burnout instrument and analyzed with paired sample t-tests. The results showed a decrease in burnout scores from a mean of 31.67 before the intervention to 25.37 in the first post-test (p = 0.005) and 25.83 in the second post-test (p = 0.007). These findings indicate that the combination of LiveWorksheet and instructional videos effectively reduced burnout by enhancing learning engagement, lowering cognitive load, and strengthening self-efficacy. Further research is recommended to use a control group design and long-term measurements to examine the sustainability of the intervention’s effects.